Mathematical modeling of some single-pulse space car flights - Nikita Yu. Isachenkov (Известия Томского политехнического университета: Промышленная кибернетика)
This paper examines the movement of a spacecraft launching from the surface of the Earth at different speeds, within the framework of the five-body problem “Sun–Earth–Moon–Mars–a body with negligible mass” with a close approach to the surface of the Moon, as well as reaching the planet Mars. The paper considers as well the movement of a spacecraft starting from the surface of the Earth at the third escape velocity, within the framework of the model of a limited plane circular problem of seven bodies “Sun–Earth–Mars–Jupiter–Saturn–Uranus–a body with negligible mass” with close approaches to the surface of Mars, Jupiter and reaching the planet Uranus. Aim. Selection of initial conditions for positions of some celestial bodies and possible initial speeds of the spacecraft for its flight from the Earth to some planets. Methods. Computer algebra (MAPLE 17 system), numerical experiments, numerical integration of differential equations using the Runge–Kutta method. Novelty. Determination of the initial speed and initial positions of the planets for reaching some planets by a spacecraft starting from the Earth. Scientific and practical significance. The results of the work can be used in practice of interplanetary flights, as well as in the research, educational and methodological work of astronomy teachers.